1998
DOI: 10.1007/s11745-998-0311-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of dietary α‐linolenic acid vs. eicosapentaenoic acid in rat immune cell phospholipids during endotoxemia

Abstract: Short-term (i.e., 3 d) continuous enteral feeding of diets containing eicosapentaenoic (EPA) and gamma-linolenic (GLA) polyunsaturated fatty acids (PUFA) to endotoxemic rats reduces the levels of arachidonic acid (AA) and linoleic acid (LA) in alveolar macrophage (AM) and liver Kupffer and endothelial (K&E) cell phospholipids with attendant decreases in prostaglandin formation by these cells in vitro. Diets that contain alpha-linolenic acid (LNA) as a substrate for endogenous formation of EPA may not be as eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…Descriptive and inferential statistics were computed on all continuous data for each parameter. The sample size was based primarily on the historical adequacy in similar studies using this model (12,13). Group differences were determined by t test and repeated measures of analysis of variance (ANOVA) across time points.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive and inferential statistics were computed on all continuous data for each parameter. The sample size was based primarily on the historical adequacy in similar studies using this model (12,13). Group differences were determined by t test and repeated measures of analysis of variance (ANOVA) across time points.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, 18:33 may in fact have different immunomodulatory properties then 20:53 and 22:63. A few reports that have directly compared 18:33 to fish oils (rich in 20:53 and 22:63) have found that they share some but not all immunomodulatory properties [9][10][11][12]. Interestingly, studies showing that 18:33 does not modulate immune function have been carried out in healthy (immunocompetent) subjects [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is important that immune formulas be initiated in a timely fashion because the physiologic effects of fish-oil supplementation on the inflammatory cell membrane may take several days to become apparent. 28 The clinician should not wait until ARDS is fully manifest before starting immunonutrition. These formulas should be started at the first signs of ALI, with aggressive advancement of infusion rate to target caloric goal.…”
Section: December 2004 571mentioning
confidence: 99%
“…Data shown as mean Ϯ SD; n ϭ 6 to 8/group. * p Ͻ .05 relative to LA and ALA (data from Palombo et al28 ). ALA, ␣-linolenic acid; EPA ϩ GLA, eicosapentaenoic acid plus ␥-linolenic acid; LA, linoleic acid; DGLA, dihomo-g-linolenic acid; AA, arachidonic acid.…”
mentioning
confidence: 99%
See 1 more Smart Citation